Design of Electronic LKPD with Integrated STEM PBL Model on Heat Material - Selvia, Selvia; Mufit, Fatni (Physics Learning and Education, 2025)
In the current era of the 21st century, rapid technological progress and the increasing complexity of life demand students to develop critical thinking, creativity, and independent problem-solving skills. Preliminary findings at SMA Negeri 1 Bonjol revealed that students still exhibit low proficiency in solving physics problems. As a solution, this study developed an Electronic Student Worksheet (LKPD) using a STEM-integrated PBL model focused on the topic of heat, aimed at enhancing students' problem-solving abilities. Employing a development and design research approach based on the Plomp model, this study aimed to design and assess the validity and practicality of the LKPD product. The results indicate that the LKPD can be effectively integrated into STEM learning, is suitable for classroom implementation, and achieved a validity score of 0.95, categorized as very valid. Practicality testing also yielded very high results, with scores of 86.41% in the one-on-one stage and 87.79% in the small group stage. Thus, the STEM-integrated PBL-based Electronic LKPD on heat material has been proven to be both valid and practical in improving students' problem-solving skills.